Global REnal Involvement of CORonavirus Disease 2019 (RECORD): A Systematic Review and Meta-Analysis of Incidence, Risk Factors, and Clinical Outcomes - Chan, Kam Wa; Yu, Kam Yan; Lee, Pak Wing; Lai, Kar Neng; Tang, Sydney Chi-Wai (Frontiers in Medicine, 2021)
Introduction The quantitative effect of underlying non-communicable diseases on acute kidney injury (AKI) incidence, and the factors affecting the odds of death among COVID-19 AKI patients were unclear at population level. This study aimed to assess the association between AKI, mortality, underlying non-communicable diseases and clinical risk factors. Methods A systematic search of 6 databases was performed from 1 January 2020 until 5 October 2020. Peer-reviewed observational studies containing quantitative data on risk factors and incidence of renal manifestations of COVID-19 were included. Location, institution and time-period were matched to avoid duplicated data source. Incidence, prevalence and odds ratio of outcomes were extracted and pooled by random-effect meta-analysis. History of renal replacement therapy (RRT) and age group were stratified for analysis. Univariable meta-regression models were built using AKI incidence as dependent variable, with underlying comorbidities and clinical presentations at admission as independent variables. Results Global incidence of AKI and RRT in COVID-19 patients were 20.40% (95%CI: 12.07 to 28.74) and 2.97% (95%CI: 1.91 to 4.04), respectively, among patients without RRT history. At population level, each percentage increase in the underlying prevalence of diabetes, hypertension, chronic kidney disease and tumour history were associated with 0.82% (95%CI: 0.40 to 1.24), 0.48% (95%CI: 0.18 to 0.78), 0.99% (95%CI: 0.18 to 1.79) and 2.85% (95%CI: 0.93 to 4.76) increased incidence of AKI across different settings, respectively. Although patients who had a kidney transplant presented with a higher incidence of AKI and RRT, their odds of mortality was lower. A positive trend of increased odds of death among AKI patients against the interval between symptom onset and hospital admission was observed. Conclusion Underlying prevalence of non-communicable diseases partly explained the heterogeneity in the AKI incidence at population level. Delay in admission after symptom onset could be associated with higher mortality among patients developed AKI, warrants further research.